Processo de registro de produtos veterinários farmacêuticos e biológicos no Brasil - Ferrari, Beatriz Helena [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
As inovações nas indústrias veterinárias são impulsionadas pelas demandas de mercado e, nesse contexto, o setor de saúde animal no Brasil tem apresentado crescimento contínuo. No entanto, para o desenvolvimento de produtos veterinários farmacêuticos e biológicos, é imprescindível que cada produto seja registrado no Ministério da Agricultura e Pecuária (MAPA). Esse órgão regulador exige que as empresas forneçam documentos comprovando os padrões de produção, qualidade, segurança, eficácia, efeitos adversos e riscos à saúde humana. Todos os dados gerados nessas etapas são compilados no relatório técnico que, em conjunto com os documentos administrativos, integra o Dossiê de Registro submetido ao MAPA. O presente estudo revisa as principais etapas do processo de registro de produtos veterinários farmacêuticos e biológicos no Brasil, com ênfase aos requisitos regulatórios a serem atendidos.

Innovations in the veterinary industry are driven by market demands and, in this context, the animal health sector in Brazil has shown continuous growth. However, in order to develop pharmaceutical and biological veterinary products, it is essential that each product is registered with the Ministry of Agriculture and Livestock (MAPA). This regulatory agency requires that companies provide documents related to production standards, quality, safety, efficacy, adverse effects and risks to human health. All the data generated in these stages is compiled into a technical report which, together with the administrative documents, forms part of the Registration Dossier submitted to MAPA. In this context, the present study provides an overview of the main steps of the registration process for pharmaceutical and biological veterinary products in Brazil, with an emphasis on the regulatory requirements to be met.
Registration process of pharmaceutical and biological veterinary products in Brazil
Keywords: Assuntos regulatórios; Indústria veterinária; Ministério da Agricultura e Pecuária; Registro de produtos veterinários; Regulatory affairs; Veterinary industry; Ministry of Agriculture and Livestock; Registration of veterinary products